2017
DOI: 10.3389/fmicb.2017.00671
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Space Flight on Survival and Interaction of Cupriavidus metallidurans CH34 with Basalt, a Volcanic Moon Analog Rock

Abstract: Microbe-mineral interactions have become of interest for space exploration as microorganisms could be used to biomine from extra-terrestrial material and extract elements useful as micronutrients in life support systems. This research aimed to identify the impact of space flight on the long-term survival of Cupriavidus metallidurans CH34 in mineral water and the interaction with basalt, a lunar-type rock in preparation for the ESA spaceflight experiment, BIOROCK. Therefore, C. metallidurans CH34 cells were sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…This balance between beneficiary and perilous change in a bacterial genome also relates to the general fitness and the energy household of its host. Members of the genus Cupriavidus , and in particular C. metallidurans , appear to be masters in adaptation as they are home to a wide variety of habitats, often in extreme conditions [ 62 , 63 , 64 , 65 ]. The introduction of the 54 kb plasmid pTP6 into a strain already carrying two large replicons of 3.9 and 2.6 Mb (chromosome and chromid, respectively) and two megasized plasmids of 171 and 234 kb (pMOL28 and pMOL30, respectively) could be seen as a serious additional burden to the host regardless of whether or not phenotypical or physiological changes occur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This balance between beneficiary and perilous change in a bacterial genome also relates to the general fitness and the energy household of its host. Members of the genus Cupriavidus , and in particular C. metallidurans , appear to be masters in adaptation as they are home to a wide variety of habitats, often in extreme conditions [ 62 , 63 , 64 , 65 ]. The introduction of the 54 kb plasmid pTP6 into a strain already carrying two large replicons of 3.9 and 2.6 Mb (chromosome and chromid, respectively) and two megasized plasmids of 171 and 234 kb (pMOL28 and pMOL30, respectively) could be seen as a serious additional burden to the host regardless of whether or not phenotypical or physiological changes occur.…”
Section: Resultsmentioning
confidence: 99%
“…The C. metallidurans genome is known to be ridden with a very high number of mobile genetic elements, with 57 IS elements, 19 other transposable elements, and 16 genomic islands for its type strain CH34 [ 12 , 32 , 34 ]. In concordance with this genomic fluidity, C. metallidurans displays a highly versatile metabolism and an inherent ability to inhabit a variety of harsh environments [ 9 , 62 , 63 , 64 , 65 ]. This adaptability has not come about overnight but is the wonderful result of microbial evolution over long periods of time.…”
Section: Resultsmentioning
confidence: 99%
“…Monitoring of the microorganisms on the space station is greatly important to evaluate risk factors for the health of astronauts and to assess material integrity of the spacecrafts (Liu, 2017). It has been reported that modeled reduced gravity and the space environment impacted microbial physiology, including growth rate, biofilm formation, antibiotic resistance, virulence, and metabolism (Byloos et al, 2017;Castro, Nelman-Gonzalez, Nickerson, & Ott, 2011;Fajardo-Cavazos, Narvel, & Nicholson, 2014;Horneck, Klaus, & Mancinelli, 2010;Orsini, Lewis, & Rice, 2017;Zea et al, 2018). The changes of microbes were adaptive responses to the microgravity environment, which allowed microbes to better accommodate the complicated environment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found as a common contaminant on the ISS ( Nickerson et al, 2004 ); (iii) Cupriavidus metallidurans CH34 (SCK CEN, Belgium), a Gram-negative, non-spore-forming, motile β-proteobacterium (phylum Proteobacteria) ( Janssen et al, 2010 ). Strains of this species have been isolated from rocks and metal-contaminated environments ( Janssen et al, 2010 ; Olsson-Francis et al, 2010 ; Bryce et al, 2016 ; Vandecraen et al, 2016 ), and it has been previously isolated from ISS and used in space experiments ( Leys et al, 2009 ; Monsieurs et al, 2014 ; Byloos et al, 2017 ). The main bacterial characteristics of the three strains are summarized ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%